2022
DOI: 10.1007/s10113-022-02011-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 lockdown on the observed density of coral reef fish along coastal habitats of Moorea, French Polynesia

Abstract: During the first COVID-19 lockdown in 2020, levels of coastal activities such as subsistence fishing and marine tourism declined rapidly throughout French Polynesia. Here, we examined whether the reduction in coastal use led to changes in fish density around the island of Moorea. Two natural coastal marine habitats (bare sand and mangrove) and one type of man-made coastal structure (embankment) were monitored on the west coast of the island before and after the first COVID-19 lockdown. At the end of the lockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Therefore, it is possible that the prolonged lockdown at Lizard Island led to a general increase in fish density due to the large reduction in human activities. Recent studies have shown a significant increase in coral reef fish densities during the lockdown period (Feeney et al, 2022; Bertucci et al, 2023). However, it is also possible that the lockdown affected the fish assemblage, which resulted in higher numbers during surveys, but this could lead to a decline in fish numbers once the lockdown is lifted and human activities resume (Lecchini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the prolonged lockdown at Lizard Island led to a general increase in fish density due to the large reduction in human activities. Recent studies have shown a significant increase in coral reef fish densities during the lockdown period (Feeney et al, 2022; Bertucci et al, 2023). However, it is also possible that the lockdown affected the fish assemblage, which resulted in higher numbers during surveys, but this could lead to a decline in fish numbers once the lockdown is lifted and human activities resume (Lecchini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The observed increases in fish biomass throughout the period of lockdown restrictions in Grand Cayman can most likely be attributed to two main reasons: (1) behavioural shifts impacting habitat distribution 26 ; and (2) improved fitness leading to increased recruitment. Firstly, cessation of water-based activities would result in reduced ambient sound and physical disturbance in the water leading to immediate changes in the behaviour of fishes that will likely become bolder and less cryptic, thereby encouraging redistribution and habitation of areas previously saturated by boats and people 35 38 . Additionally, reductions in stressful conditions caused by water-based activities, such as noise and waste from large boats, also impacts key behaviours including feeding, sociality, reproduction, and subsequently, physiology 21 23 , 31 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In summary, lockdown restrictions on water-based activities in response to COVID-19 are associated with increased biomass of coral reef fish, particularly parrotfish and juvenile parrotfish. Given the clear ubiquitous impacts of COVID-19 lockdowns around the world on behaviour and physiology of multiple organisms across multiple ecosystems 27 , 28 , increased biomass of reef fish is not surprising 35 38 . However, our study highlights the effect over a longer time-period (2 years) than previous studies 35 37 (~ 3 months), indicating increased biomass was likely driven by both altered behaviour and increased ecological fitness owing to lockdown restrictions, which subsequently contributed to fish recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation